Preparation method of lithium sulfide and application of lithium sulfide in lithium-sulfur battery
By combining chitin and its derivatives with lithium sulfate, lithium sulfide powder is prepared through carbonization coating and redox reaction, the polysulfide shuttle effect and lithium dendrites in lithium sulfur batteries are solved, and the lithium sulfur battery is significantly improved Specific capacity and cycle stability achieve safe, environmentally friendly, low-cost and efficient preparation.
Patent Information
- Application Number
- CN202411273897.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Lithium sulfur batteries have insufficient irreversible capacity and cycle stability due to the shuttle effect of polysulfide and dendrite problems of lithium metal, which limits their application, and the insulating characteristics of lithium sulfide limits the research.
Chitin and its derivatives are used as carbon source to recombinate with lithium sulfate, and lithium sulfide powder is prepared through carbonization coating and redox reaction to improve its electronic conductivity and cycle stability.
The specific capacity and cycle stability of the lithium-sulfur battery positive electrode material are significantly improved, and the specific capacity after circulation reaches 778mAh/g, and the preparation process is safe, environmentally friendly, low-cost, and easy to industrially produce.
Smart Images

Figure CN119118069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium sulfide preparation, in particular to a method for preparing lithium sulfide and application of the lithium sulfide in a lithium-sulfur battery. Background Art
[0002] To date, lithium-ion batteries are still the most widely used batteries in commercial applications. However, with economic development and social progress, their low energy density (200-250Wh / kg) can no longer meet the society's requirements for high-energy-density batteries. Therefore, it is urgent to explore new high-energy-density battery systems. Among the many battery systems, lithium-sulfur batteries are the most popular. Lithium-sulfur batteries are a type of rechargeable lithium battery. Generally, elemental sulfur is used as the positive electrode active material of the battery and metallic lithium is used as the negative electrode active material. They have the advantages of light weight, large capacity, and no memory effect. The specific energy of lithium-sulfur batteries is much higher than that of lithium-ion batteries widely used in commercial applications. It is a very promising high-energy battery. Lithium-sulfur batteries have high energy density (2600Wh / kg) and volume density (2800Wh / L), which are twice that of commercial lithium-ion batteries. The sulfur positive electrode has a theoretical capacity of 1675mAh / g, and it is also inexpensive and environmentally friendly, and has also attracted much attention.
[0003] However, lithium-sulfur batteries have some intrinsic defects that hinder their further development: (1) The shuttling effect of polysulfides leads to the generation of irreversible capacity, reduces coulombic efficiency, and greatly limits its cycle stability; (2) The problem of lithium metal dendrites leads to the rupture of the diaphragm and reduces the safety performance of the battery. Therefore, lithiated lithium sulfide positive electrodes came into being, which can be matched with negative electrodes such as Si, Al, and graphite, thereby avoiding the use of lithium metal, solving the lithium dendrite problem at the source, and greatly improving the safety performance of the battery.
[0004] Lithium sulfide is a sulfide of lithium, with a molecular formula of Li2S, a molecular weight of 45.95, white to yellow crystals, and an inverse CaF2 crystal structure. Its density is 1.63g / cm3, melting point is 938°C, boiling point is 1372°C, and it is soluble in ethanol, soluble in acid, and insoluble in alkali. However, the use of lithium sulfide as a positive electrode has not yet solved the shuttle effect of polysulfides, and the insulating properties of lithium sulfide further limit its research. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing lithium sulfide, which uses chitosan and its derivatives as a carbon source, composites with lithium sulfate and lithium sulfide, synthesizes lithium sulfate powder, and improves the electronic conductivity of the active material. The method is low-cost, simple in process, and can be used for large-scale production of lithium sulfide.
[0006] In order to achieve the purpose of the above invention, a method for preparing lithium sulfide has the following main steps:
[0007] S1. Raw material grinding:
[0008] Grinding and mixing lithium sulfate and chitosan or a chitosan derivative;
[0009] S2, carbonization coating reaction:
[0010] The mixture ground and mixed in step S1 is placed in a corundum crucible, the corundum crucible is placed in a tube furnace, heated to 220-250° C. in a nitrogen atmosphere, kept constant for 1 hour, and then heated to 280-310° C. in a nitrogen atmosphere for 5 hours to perform a carbonization coating reaction;
[0011] S3, redox reaction:
[0012] The mixture after the carbonization coating reaction in step S2 is heated to 650-750° C. in a nitrogen atmosphere, kept at the constant temperature for 10 hours for oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0013] The present invention provides for the first time a method for synthesizing lithium sulfate powder using chitosan and its derivatives as carbon sources and lithium sulfate. The inventors have made a significant discovery in a large number of experiments that lithium sulfide powder is obtained by mixing chitosan and its derivative powders with lithium sulfate powder, and then carbonizing, coating, oxidizing, reducing and grinding. When lithium sulfide powder is used as a positive electrode material for lithium-sulfur batteries, it exhibits a high specific capacity and cycle stability; specific experimental studies have shown that when lithium sulfide powder is used as a positive electrode material for lithium-sulfur batteries, it has a high specific capacity, and after 100 cycles, the specific capacity is 778mAh / g, and the cycle performance is excellent.
[0014] In addition, the inventors need to emphasize that the above-mentioned reaction steps described in the present invention are very critical and indispensable. The lithium sulfide prepared without any step does not have excellent cycle performance when used as a positive electrode material for lithium-sulfur batteries. Using chitosan and its derivatives as carbon sources, chitosan and its derivative powders and lithium sulfate powders are first mixed, and then carbonization coating, oxidation-reduction and grinding are performed to prepare lithium sulfide powder, which has excellent cycle performance when used as a positive electrode material for lithium-sulfur batteries.
[0015] Specifically, in step S1, the chitosan derivative is chitosan, carboxymethyl chitosan, carboxymethyl chitosan, quaternary ammonium chitosan or quaternary ammonium chitosan.
[0016] Furthermore, in step S1, the specific method of grinding and mixing is hand grinding, ball grinding, air flow grinding or mechanical grinding.
[0017] Specifically, in step S1, the molar ratio of lithium sulfate to chitosan or the molar ratio of lithium sulfate to chitosan derivative is 1:(0.5-2).
[0018] Furthermore, in step S1, the molar ratio of lithium sulfate to chitosan or the molar ratio of lithium sulfate to chitosan derivative is 1:0.5.
[0019] Specifically, in step S2, the mixture ground and mixed in step S1 is placed in a corundum crucible, the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere for 1 hour, and then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for 5 hours to carry out a carbonization coating reaction.
[0020] Specifically, in step S3, the mixture after the carbonization coating reaction in step S2 is heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at a constant temperature for 10 hours to perform a redox reaction, and finally ground to obtain lithium sulfide.
[0021] Another object of the present invention is to provide application of lithium sulfide prepared according to the above preparation method in lithium-sulfur batteries.
[0022] Specifically, the lithium sulfide is used as the positive electrode material of a lithium-sulfur battery.
[0023] The method for preparing lithium sulfide of the present invention has the following advantages compared with the prior art:
[0024] (1) For the first time, a method for synthesizing lithium sulfate powder using chitosan and its derivatives as carbon sources and lithium sulfate is provided. The inventors have made significant discoveries in a large number of experiments. Chitosan and its derivative powders are mixed with lithium sulfate powders, and then carbonized, coated, oxidized, reduced and ground to obtain lithium sulfide powders. When the lithium sulfide powders are used as positive electrode materials for lithium-sulfur batteries, they exhibit high specific capacity and cycle stability. Specific experimental studies have shown that when lithium sulfide powders are used as positive electrode materials for lithium-sulfur batteries, they have high specific capacity. After 100 cycles, the specific capacity is 778 mAh / g, and the cycle performance is excellent.
[0025] (2) Chitosan and its derivative powders are mixed with lithium sulfate powder, and then carbonized, coated, oxidized, reduced and ground to obtain lithium sulfide powder, which has high specific capacity and cycle stability when used as a positive electrode material for lithium-sulfur batteries;
[0026] (3) The method described in the present invention is safe, environmentally friendly, easy to operate, low in preparation cost, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an appearance diagram of the lithium sulfide powder prepared in Example 1 of the present invention;
[0028] Figure 2 This is the XRD pattern of the lithium sulfide powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0030] Example 1
[0031] Lithium sulfate and chitosan are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tube furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere for 1 hour, and then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for 5 hours for carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for oxidation-reduction reaction, and finally ground to obtain lithium sulfide, such as Figure 1 Its XRD pattern is shown in Figure 2 shown.
[0032] Example 2
[0033] Lithium sulfate and chitosan are ground and mixed in a molar ratio of 1:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for a carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for an oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0034] The difference between Example 2 and Example 1 is that the molar ratio of lithium sulfate and chitosan in Example 2 is 1:1; while the molar ratio of lithium sulfate and chitosan in Example 1 is 2:1.
[0035] Example 3
[0036] Lithium sulfate and chitosan are ground and mixed in a molar ratio of 3:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for a carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for an oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0037] The difference between Example 3 and Example 1 is that the molar ratio of lithium sulfate and chitosan in Example 3 is 3:1; while the molar ratio of lithium sulfate and chitosan in Example 1 is 2:1.
[0038] Example 4
[0039] Lithium sulfate and chitosan are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere and kept at a constant temperature for 5 hours for carbonization coating reaction, and then heated to 650°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at a constant temperature for 10 hours for redox reaction, and finally ground to obtain lithium sulfide.
[0040] The difference between Example 4 and Example 1 is that the oxidation-reduction reaction temperature of Example 4 is 650°C; while the oxidation-reduction reaction temperature of Example 1 is 700°C.
[0041] Example 5
[0042] Lithium sulfate and chitosan are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere and kept at a constant temperature for 5 hours for carbonization coating reaction, and then heated to 750°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at a constant temperature for 10 hours for redox reaction, and finally ground to obtain lithium sulfide.
[0043] The difference between Example 5 and Example 1 is that the oxidation-reduction reaction temperature of Example 5 is 750°C; while the oxidation-reduction reaction temperature of Example 1 is 700°C.
[0044] Comparative Example 1
[0045] Lithium sulfate and sucrose are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for a carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for an oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0046] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, sucrose is used as the carbon source, while in Example 1, chitosan is used as the carbon source.
[0047] Comparative Example 2
[0048] Lithium sulfate and glucose are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for a carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for an oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0049] The difference between Comparative Example 2 and Example 1 is that glucose is used as the carbon source in Comparative Example 2, while chitosan is used as the carbon source in Example 1.
[0050] Comparative Example 3
[0051] Lithium sulfate and maltose are ground and mixed in a molar ratio of 2:1, and then the mixture is put into a corundum crucible, and the corundum crucible is placed in a tubular furnace, and heated to 250°C at a heating rate of 7°C / min under a nitrogen atmosphere and kept at a constant temperature for 1 hour, then heated to 300°C at a heating rate of 1°C / min under a nitrogen atmosphere for a carbonization coating reaction, and then heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere for 10 hours for an oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
[0052] The difference between Comparative Example 3 and Example 1 is that maltose is used as the carbon source in Comparative Example 3, while chitosan is used as the carbon source in Example 1.
[0053] The lithium sulfide prepared in the above Examples 1 to 5 and Comparative Examples 1 to 3 was used as the positive electrode material of the lithium-sulfur battery, PVDF was used as a binder, conductive carbon black SP was used as a conductive agent, and NMP was used as a solvent to slurry and coat the positive electrode on aluminum foil to make a positive electrode. The half-cell with a metal lithium disc as the counter electrode was subjected to electrochemical testing, and 1M LiTFSI+DOL / DME (1:1) was used as the electrolyte. The positive electrode, electrolyte, diaphragm, and lithium sheet were sequentially added to the positive electrode shell for battery assembly. After assembly, the battery was compressed and sealed in a fully automatic packaging machine. After standing for 24 hours, the battery performance was tested using a blue electric test system. The electrochemical test was carried out at a constant temperature of 25°C, the battery test voltage range was 1.7-2.8V relative to (Li / Li+), the cycle test current was 0.5C, and the discharge specific capacity (mAh / g) was tested after 500 cycles. The test results are shown in Table 1.
[0054] Table 1
[0055]
[0056]
[0057] It can be seen from the experimental data in Table 1 that when the lithium sulfide prepared in Example 1 is used as the positive electrode material of the lithium-sulfur battery, the first coulombic efficiency is 96% at a current density of 0.5C, the first discharge specific capacity is 1182mAh / g, the discharge specific capacity after 500 cycles is 827mAh / g, and the discharge specific capacity retention rate is 70%. This shows that the lithium sulfide prepared by the method described in the present invention using chitosan as a carbon source exhibits very excellent cycle performance and high specific capacity when used as a positive electrode material for a lithium-sulfur battery.
[0058] When the lithium sulfide prepared in Examples 1 and 2-3 is used as the positive and negative electrode materials of lithium-sulfur batteries, the research and analysis found that the molar ratio of lithium sulfate and chitosan has an important influence on the performance of lithium sulfide. The first coulomb efficiency, first discharge specific capacity, discharge specific capacity after 500 cycles and discharge specific capacity retention rate of the lithium sulfide in Examples 2-3 are much smaller than those of the lithium sulfide in Example 1. This shows that in the process of preparing lithium sulfide by the method described in the present invention, the selection of the molar ratio of lithium sulfate and chitosan plays an important role in whether the prepared lithium sulfide has excellent cycle performance when used as the positive and negative electrode materials of lithium-sulfur batteries. When the molar ratio of lithium sulfate and chitosan is selected to be 2:1, the prepared lithium sulfide has excellent cycle performance, high first coulomb efficiency, high first discharge specific capacity and high discharge specific capacity retention rate when used as the positive and negative electrode materials of lithium-sulfur batteries. The main reason is that when the molar ratio of lithium sulfate and chitosan is lower than 2:1, the synthesized carbon content is too high, which will cause the lithium sulfide content of the active material to be too low. When the molar ratio of lithium sulfate and chitosan is higher than 2:1, the lithium sulfate reaction is insufficient, which also causes the lithium sulfide content of the active material to be too low.
[0059] When the lithium sulfide prepared in Examples 1 and 4-5 is used as the positive and negative electrode materials of lithium-sulfur batteries, the research and analysis found that the redox reaction temperature has an important influence on the performance of lithium sulfide. The first coulomb efficiency, first discharge specific capacity, discharge specific capacity after 500 cycles and discharge specific capacity retention rate of the lithium sulfide in Examples 4-5 are much lower than those of the lithium sulfide in Example 1. This shows that in the process of preparing lithium sulfide by the method described in the present invention, a redox reaction temperature that is too high or too low is not conducive to the construction of a perfect lithium sulfide structure, and a redox reaction temperature of 700°C is conducive to lithium sulfide obtaining excellent lithium storage performance.
[0060] The study of Example 1 and Comparative Examples 1 to 3 found that the first coulombic efficiency, first discharge specific capacity, discharge specific capacity after 500 cycles and discharge specific capacity retention rate of lithium sulfide prepared by using chitosan as a carbon source are much better than those prepared by using sucrose, glucose and maltose as carbon sources. This shows that the choice of carbon source has a great influence on the performance of the prepared lithium sulfide. Chitosan as a carbon source is conducive to improving the structure of lithium sulfide, and the perfect lithium sulfide structure is conducive to the insertion and extraction of lithium ions.
Claims
1. A method for preparing lithium sulfide, characterized in that: The main steps are as follows: S1. Raw material grinding: Grinding and mixing lithium sulfate and chitosan or a chitosan derivative; S2, carbonization coating reaction: The mixture ground and mixed in step S1 is placed in a corundum crucible, the corundum crucible is placed in a tube furnace, heated to 220-250° C. in a nitrogen atmosphere, kept constant for 1 hour, and then heated to 280-310° C. in a nitrogen atmosphere for 5 hours to perform a carbonization coating reaction; S3, redox reaction: The mixture after the carbonization coating reaction in step S2 is heated to 650-750° C. in a nitrogen atmosphere, kept at the constant temperature for 10 hours for oxidation-reduction reaction, and finally ground to obtain lithium sulfide.
2. The method for preparing lithium sulfide according to claim 1, characterized in that: In step S1, the chitosan derivative is chitosan, carboxymethyl chitosan, carboxymethyl chitosan, quaternary ammonium chitosan or quaternary ammonium chitosan.
3. The method for preparing lithium sulfide according to claim 2, characterized in that: In step S1, the specific method of grinding and mixing is hand grinding, ball grinding, air flow grinding or mechanical grinding.
4. The method for preparing lithium sulfide according to claim 1, characterized in that: In step S1, the molar ratio of lithium sulfate to chitosan or the molar ratio of lithium sulfate to chitosan derivative is 1:(0.5-2).
5. The method for preparing lithium sulfide according to claim 4, characterized in that: In step S1, the molar ratio of lithium sulfate to chitosan or the molar ratio of lithium sulfate to chitosan derivative is 1:0.
5.
6. The method for preparing lithium sulfide according to claim 1, characterized in that: In step S2, the mixture ground and mixed in step S1 is placed in a corundum crucible, the corundum crucible is placed in a tubular furnace, heated to 250°C at a heating rate of 7°C / min in a nitrogen atmosphere and kept at a constant temperature for 1 hour, and then heated to 300°C at a heating rate of 1°C / min in a nitrogen atmosphere and kept at a constant temperature for 5 hours to perform a carbonization coating reaction.
7. The method for preparing lithium sulfide according to claim 6, characterized in that: In step S3, the mixture after the carbonization and coating reaction in step S2 is heated to 700° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and kept at a constant temperature for 10 hours for redox reaction, and finally ground to obtain lithium sulfide.
8. An application of lithium sulfide in a lithium-sulfur battery, characterized in that: The lithium sulfide is prepared by the preparation method according to any one of claims 1 to 7.
9. The use of lithium sulfide in a lithium-sulfur battery according to claim 7, characterized in that: The lithium sulfide is used as the positive electrode material of the lithium-sulfur battery.
Citation Information
Patent Citations
Method for preparing nanometer silicon carbide at low temperature
CN109748282A
Preparation method and application of lithium sulfide
CN117509686A
Nanometer silicon-silicon monoxide-carbon composite negative electrode material, preparation method and lithium battery
CN118315550A
Method of producing lithium sulfide, and raw material of producing lithium sulfide
JP2023132283A
Composition for improving joint health by reducing body fat in companion dogs
KR102582313B1
Cited By
Electronic-grade lithium sulfide and preparation method and application thereof
CN120483052A
Method for preparing high-purity lithium sulfide at high temperature and low pressure
CN121651282A
